An assessment of the impact of herb-drug combinations used by cancer patients. Issue 1 (December 2016) - Alsanad, Saud; Howard, Rachel; Williamson, Elizabeth
Abstract Background Herb/Dietary Supplements (HDS) are the most popular Complementary and Alternative Medicine (CAM) modality used by cancer patients and the only type which involves the ingestion of substances which may interfere with the efficacy and safety of conventional medicines. This study aimed to assess the level of use of HDS in cancer patients undergoing treatment in the UK, and their perceptions of their effects, using 127 case histories of patients who were taking HDS. Previous studies have evaluated the risks of interactions between HDS and conventional drugs on the basis on numbers of patient using HDSs, so our study aimed to further this exploration by examining the actual drug combinations taken by individual patients and their potential safety. Method Three hundred seventy-five cancer patients attending oncology departments and centres of palliative care at the Oxford University Hospitals Trust (OUH), Duchess of Kent House, Sobell House, and Nettlebed Hospice participated in a self-administered questionnaire survey about their HDS use with their prescribed medicines. The classification system of Stockley's Herbal Medicine's Interactions was adopted to assess the potential risk of herb-drug interactions for these patients. Results 127/375 (34 %; 95 % CI 29, 39) consumed HDS, amounting to 101 different products. Most combinations were assessed as 'no interaction', 22 combinations were categorised as 'doubt about outcomes of use', 6 combinations as 'Potentially hazardous outcome', one combination as an interaction with 'Significant hazard', and one combination as an interaction of "Life-threatening outcome". Most patients did not report any adverse events. Conclusion Most of the patients sampled were not exposed to any significant risk of harm from interactions with conventional medicines, but it is not possible as yet to conclude that risks in general are over-estimated. The incidence of HDS use was also less than anticipated, and significantly less than reported in other areas, illustrating the problems when extrapolating results from one region (the UK), in one setting (NHS oncology) in where patterns of supplement use may be very different to those elsewhere.